Metabolic endotoxemia and cardiovascular disease: A systematic review about potential roles of prebiotics and probiotics - Moludi, Jalal; Maleki, Vahid; Jafari‐Vayghyan, Hamed; Vaghef‐Mehrabany, Elnaz; Alizadeh, Mohammad (Clinical and experimental pharmacology & physiology, 2020)
Translocation of microbiome‐derived lipopolysaccharide (LPS) to the bloodstream (metabolic endotoxaemia) is associated with a significantly increased risk of cardiovascular diseases (CVD); however, the direction of this association is not fully understood. It has been revealed by some studies that alterations in the intestinal microbiota (dysbiosis) lead to increased intestinal permeability and translocation of LPS to the blood circulation. LPS may trigger toll‐like receptor 4‐ (TLR‐4) mediated inflammatory responses; this could lead to a chronic low‐grade pro‐inflammatory condition named metabolic endotoxaemia (ME), which is typically observed in CVD patients. ME is promoted by increased intestinal permeability. Moreover, dysbiosis leads to production of trimethylamine‐N‐oxide (TMAO), a gut bacterial metabolite suggested as a new risk factor in CVD development. Probiotics, extensively reviewed for decades, are live microorganisms which, when taken in adequate amounts, have beneficial effects on the host metabolism. Prebiotics are a type of dietary fibre that act as nourishment for the good bacteria in the gut and decrease the population of pathogen bacteria that produce greater amounts of endotoxins. Although an association has been postulated between ME and CVD, the results of studies investigating the role of antibiotic therapy in preventing the disease have been inconsistent. In this review, we discuss how prebiotics and probiotics modulate gut microbiota and consequently might help with prevention and/or treatment of CVD associated with ME.